One Health approach to Coxiella burnetii: first serosurvey of owners and dogs living on oceanic islands and mainland seashore areas of Brazil - Freitas, Aaronson Ramathan; França, Danilo Alves de; Kmetiuk, Louise Bach; Martini, Rafaella; Delai, Ruana R.; Pimpão, Claudia Turra; Perotta, João Henrique; Roque de Barros-Filho, Ivan; Figueiredo, Fabiano Borges; Giuffrida, Rogério; Santarém, Vamilton Alvares; Langoni, Helio; et al. (Frontiers in Public Health, 2025)
Coxiella burnetii, the causative agent of Q fever, a zoonotic pathogen with primarily airborne transmission and diverse host species, have been reported in serosurveys of vulnerable populations worldwide. Although vulnerable populations from oceanic islands and mainland seashore areas in Brazil may be also exposed C. burnetti, no study to date has concomitantly assessed owners and dogs in such environmental setting. Accordingly, the present study aimed to assess the C. burnetii seroprevalence in owners and their dogs from oceanic islands and mainland seashore areas of southern Brazil. Overall, 5/335 (1.49%) humans and none/352 (0%) dogs of three oceanic islands and two mainland coastal areas were seropositive to anti-Coxiella burnetii antibodies by Indirect Immunofluorescence Assays (IFA). Such low seroprevalence may have been consequence of the livestock absence of these environmentally preserved islands, in addition to a major geographical barrier to airborne dispersal in southern Brazilian seashore mainland areas due to the rainforest (Serra do Mar) mountains. Finally, absence of dog seropositivity herein, suggesting that seropositive humans were exposed to C. burnetti outside these islands and seashore mainland areas, may provide new insights of C. burnetii transmission, disease cycle and prevention.